To Evaluate the Hypertension, Diabetes, and Urinary Tract Infection Anemia Effect on Kidney Function a Retrospective-based Study (Asian Journal of Pharmaceutics (AJP), 2023)
Aim: Few researches have been done on the effects of various illnesses on renal function. This key aspect istaken into account for the conduct of our study, and it aids in the continuation of our research and provides abrief overview of the prevalence and predominance of renal failure. The types of renal damage that are morecommon were described in relation to diseases, age, sex, and social behavior to rule out diseases that causerenal damage. Methodology: At the Suraksha Hospital in Andhra Pradesh’s nephrology department, a nonexperimentalprospective observational study was carried out. The duration of the study was roughly 3 years. Inthe study, 1000 patients were included depending on their diseases, age, sex, and social behavior. Results: Ourresearch identified disorders that affect renal function. Males are more likely to have disorders that affect kidneyfunction, and the 50–70 age bracket is particularly important. Diabetes mellitus (DM) left untreated impairskidney function. Conclusions: Data show that patients between the ages of 50 and 70 were most affected, whereasthose older than 70 were less affected. There were 1000 individuals diagnosed with a renal injury, and out of those,600 (or 60%) were men and 400 (or 40%) were women. Out of 1000 individuals with renal failure, 625 are locatedin rural areas, whereas 375 are located in urban areas. DM patients (680, or 68%), hypertension (190, or 19%),urinary tract infection (100, or 10%), and anemia (3%) are the conditions that cause kidney failure.